STRATEGI MARKETING COMMUNICATION DALAM PROSES CLIENT SERVICE DI RADIO TRAX FM PALEMBANG DALAM MENINGKATKAN KERJASAMA - Rahma Santhi Zinaida; Muhammad Athallah Zada Pandya2 (Media Bina Ilmiah, 2024)
Broadcast radio is an aspect that originates from communication, and broadcast radio must develop in a way that is more than just satisfying and shaping public tastes because radio is a component of mass communication media that has reciprocal roles and relationships, but also plays a role in forming opinions and social governance. In the midst of tight competition for broadcast radio in getting clients, Radio Trax FM can take advantage of existing opportunities by using positioning as a youth radio or radio for young people aged 15 - 25 years (men and women). As a private broadcast radio in Indonesia, Trax FM radio has main competitors whose listener segmentation is the same. Radio stations have similar segmentation and positioning, so they are required to compete. Radio Trax Fm also carries out promotional activities such as Advertising, Sales Promotion, Direct Marketing, Interactive Marketing, Public Relations and Personal Sales, which are activities to attract client interest. This marketing strategy is one of the factors to determine the success or failure of a company. Based on the background thinking above, the author took the title "Marketing Communication Strategy in the Client Service Process at Trax Fm Radio Palembang To Increase Collaboration